2009 개정 교육과정 고등학교 융합형 과학에 대한 교사와 학생의 인식 및 수업 운영 실태조사 - 엄희숙; 문성배; Eoum, Hee-sook; Moon, Seong-Bae (대한지구과학교육학회지, 2014)
This study investigates the implementation of the Converged Science, and what teachers and students think of it in order to understand how it is taking root in schools. The results identify ways in which the new curriculum can establish itself in schools. One hundred and two science teachers, who had participated in the mandatory workshop for the 2009 Amended Course of Science, were given the first survey regarding their general perception of the converged science curriculum. A year after the first implementation of the new curriculum, one hundred and seventy one science teachers were given the second survey in order to determine their general perception and actual results in the classrooms. A similar survey was given to one hundred and forty nine tenth grade students. In addition, one hundred and forty eight tenth grade students, who had experienced the new science curriculum, took part in another survey revealing their general thoughts the course. The results show that the teachers' responses are rarely positive. The teachers claimed that the contents were too extensive while the level of fundamental concepts were too rigorous for tenth graders. They also asserted that the contents contained too much of a particular subject, and that it is necessary to lower the level of rigor. With regard to the level of unification of converged science textbooks, the teachers expressed that they are still slightly inadequate. The subject of science in the seventh curricula was criticized due to its lack of convergence: over 90% of the respondents answered negatively. On the other hand, the students responded more positively: they said that the new converged science was difficult to learn, but was interesting. In Busan, most high schools adopted the new curriculum in the first year when it was introduced for the first time. In most cases (over 80%), several teachers divided and taught the contents either according to their majors or regardless of their majors.